Integration of Meaning Change Analysis in Language Education: A Pedagogical Approach to Improving Students' Critical Thinking Skills Through Comedy-Based Learning - Faizah, Umi; Harsandi, Tsalaatsa ‘Ashri; Sholeh, Khabib; Kadaryati, Kadaryati; Bagiya, Bagiya (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research aims to explore the integration of the analysis of meaning changes in language learning through comedy media as a contextual and reflective pedagogical approach. Using a mixed-methods design, the study involved 250 high school students from urban and rural backgrounds divided into experimental and control groups. Data were collected through linguistic corpus analysis (N > 10,000 units), pretest–posttest, in-depth interviews, and learning observations. Data analysis was performed quantitatively with paired t-tests, hierarchical regression, and qualitative thematic analysis using NVivo software. The results showed that students in the experimental group experienced a significant improvement in their ability to interpret contextual and metaphorical meanings (p < 0.001, d Cohen = 1.2). Visualizations such as heatmaps, word clouds, and semantic networks show that words such as body, bolt, and Jockey undergo complex expansion of meaning and can be read as representations of social change. These findings show that educational humor has strong potential as a language learning medium that builds critical literacy, broadens semantic insights, and enhances students' empathy for socio-cultural issues. This study concludes that comedy-based semantic approaches are effective for vocabulary mastery and relevant in shaping a generation of learners sensitive to the dynamics of language and meaning in social life.